BIBLIOMETRIC ANALYSIS IN TAXATION RESEARCH: TAX ACCOUNTING TRENDS - Susanto, Febry Fabian (JURNAL AKUNTANSI DAN SISTEM INFORMASI, 2025)
This study uses a bibliometric approach to analyze trends and research networks in tax accounting based on Scopus data for 2014–2024. The analysis results show an annual growth of publications of 10.13%, with contributions from academics in the United States and Australia, especially from Macquarie University and Brigham Young University. The Journal of the American Taxation Association is the primary source of publications. At the same time, keywords such as tax system, carbon emissions, and fiscal policy reflect the shift in research towards environmental tax policy. The document with the highest citation is Saez E (2016) in the Quarterly Journal of Economics, which has 761 citations and discusses progressive tax policy and income distribution. The most productive researchers are Shevlin Terry and Freudenberg Brett, each producing several publications in various years. The collaboration network highlights Hanlon Michelle as one of the influential authors, with studies focusing on the impact of taxation on macroeconomic and business policies. The results of this study provide systematic insights into the pattern of tax accounting research, supporting academics in determining research directions and policymakers in designing evidence-based tax regulations.